Fenomena Campur Kode dalam Video “Cara Marshanda Merawat Kesehatan Mental Diri Sendiri” pada kanal YouTube Menjadi Manusia - Gadis artika; Dian Aurelia; Yupita Aswalia; Ida Basaria (Jurnal Riset Rumpun Ilmu Bahasa, 2026)
Data was collected through the listening method with the recording technique, then analyzed using mixed code theory in sociolinguistic studies. Data was analyzed using mixed code theory in sociolinguistic studies to reveal language usage patterns in the context of digital media. The research results show that code mixing serves as a multidimensional communicative strategy. First, mixing code is used to express emotions more effectively and authentically. Second, it serves to clarify the meaning of psychological concepts that do not have the right equivalent in Indonesian. Third, build closeness with an audience that has a bilingual background. Fourth, constructing a bilingual identity of speakers that reflects the social reality of Indonesian urban society. This research contributes to the understanding of the language practice of the Indonesian bilingual community in the digital era, especially in the delivery of personal and sensitive issues such as mental health, which requires a flexible and relatable communication strategy for millennial audiences and generation Z.